2019
DOI: 10.18203/2349-2902.isj20190820
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological study of multinodular goitre

Abstract: Background: Multinodular goitre (MNG) is a clinicopathological entity characterized by an increased volume of the thyroid gland with formation of nodules. The present study has been planned to study the various clinical presentations and diagnostic accuracy between operative findings and histopathological findings in a case of multinodular goitre.Methods: The present study was a hospital-based prospective study conducted in Dr D.Y. Patil Medical College, Hospital and Research Centre, Pune between July 2016 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 3 publications
3
8
0
Order By: Relevance
“…Kapoor et al, reported Total Thyroidectomy is the most common procedure found and incidence of malignancy in 14% cases 18 . These results were similar to a study done by Athavale et al 9 , and a similar trend was reported in this study as well.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Kapoor et al, reported Total Thyroidectomy is the most common procedure found and incidence of malignancy in 14% cases 18 . These results were similar to a study done by Athavale et al 9 , and a similar trend was reported in this study as well.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, among 37 cases of malignancy, 13 were males and 24 were females with a male to female ratio of 1:2 in line with other national and international studies 9 . The frequency of malignant thyroid carcinoma on histopathological examination was 31.8% in our study which was slightly higher than other similar studies in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the study conducted by Athavale et al in 2019, majority of cases belong to the 3 rd and 2 nd decades, least was in the 6 th decade. 8 Kondur et al reported that out of 103 cases, 36% cases were in the age group of 30-39 years with maximum distribution in the third decade and least in the 6 th decade (4%). 9 In the study conducted by Amudhan et al in 2017, majority of cases belonged to the 3 rd and 4 th decades; least was in the 6th decade.…”
Section: Discussionmentioning
confidence: 99%
“…After confirmation, as a first line of treatment among different type of surgeries total thyroidectomy was preferred in case of malignancy. In this technique complete malignant part of the gland was removed to reduce recurrence rate 26 .…”
Section: Discussionmentioning
confidence: 99%